Effect of Good Corporate Governance Mechanism on Banking Financial Performance with Risk Management as an Intervening Variable - Paulina Paulina; Rika Septafani; Devita Meliana R; Anindya Prihandini; Raynaldo Free Altiro; Gita Chairunnisa (Jurnal Ilmu Manajemen dan Ekonomika, 2020)
This study aims to determine the effect of Good Corporate Governance (GCG) mechanisms on Banking Financial Performance with Risk Management as a intervening variable. GCG in this study is measured by three indicators namely Managerial Ownership, Institutional Ownership, and the Proportion of Independ-ent Board of Commissioners, while the Banking Financial Performance is measured by Return on Asset (ROA), and Risk Management is measured by Non Performing Loan (NPL). The population in this study are all banking companies listed in Indonesia Stock Exchange for the period of 2016 - 2019. The sample in this study was selected using purposive sampling which obtained a sample of 19 banks from a total of 43 banks that were used as sample in this study. Data analysis techniques in this study using panel data analy-sis. The results of this study stated that Managerial Ownership and the Proportion of Independent Board of Commissioners partially have a negative effect on Banking Financial Performance. While Institutional Ownership does not have an effect on Banking Financial Performance. Risk Management as a intervening variable can affect the relationship between Managerial Ownership with Banking Financial Performance and the relationship between the Proportion of Independent Board of Commissioners with Banking Finan-cial Performance. However, Risk Management cannot affect the relationship between Institutional Owner-ship with Banking Financial Performance.